Is trust in companies rooted in social trust, or regulatory quality, or both? - Markus Leibrecht; Hans Ptilik (Austrian Institute of Economic Research (WIFO), 2018)
While trust in the business sector is crucial for well-functioning markets, there is surprisingly little empirical work on its sources. Available research recognises social trust as a major force explaining confidence in political institutions. Regulation is frequently advocated to foster trust in companies as it is supposed to reduce scope for opportunistic behaviour. Based on individual level data from World Values Survey, European Values Studies and economic regulation data from the Economic Freedom of the World project the paper empirically investigates joint effects of social trust, intensity and quality of regulation on public trust in major companies. Our findings suggest that it is not the intensity of economic regulation per se which matters for trust in companies but that the impartiality with which rules are enforced is decisive, even when we control for social trust. Trust in business can be facilitated by an implicit guarantee of governments to fair and impartial treatment.
Keywords: D90; L50; P12; 330; Social Trust; Trust in Companies; Economic Regulation; World Values Survey